Post-Divorce Family Resilience: Uncovering the Dynamics of Recovery and Strenght from a Literature Review Perspective - Pranata, Dwi Chandra; Fairuzzaman, Riza Reyhan; Hartini, Nurul (Psikostudia : Jurnal Psikologi, 2025)
This study explores family resilience post-divorce and the contributing factors to their emotional and psychological adaptation. A literature review method was utilized, analyzing 14 journal articles. The findings reveal significant roles of social support, emotional regulation, and coping skills in fostering resilience. Families who receive strong social support tend to recover more effectively from the emotional distress caused by divorce. Emotional regulation and positive coping strategies also enable family members, particularly children, to adapt better to changes. Interventions targeting these three factors have been shown to accelerate recovery and adaptation processes. This research emphasizes the importance of supporting families through systematic and tailored approaches to enhance resilience and mitigate the adverse effects of divorce. Penelitian ini mengeksplorasi resiliensi keluarga pasca perceraian dan faktor-faktor yang berkontribusi terhadap adaptasi emosional dan psikologis mereka. Metode kajian literatur digunakan dengan menganalisis 14 artikel jurnal. Hasil penelitian menunjukkan peran signifikan dukungan sosial, regulasi emosi, dan keterampilan coping dalam membangun resiliensi. Keluarga yang mendapatkan dukungan sosial yang kuat cenderung lebih efektif pulih dari tekanan emosional akibat perceraian. Regulasi emosi dan strategi coping yang positif juga memungkinkan anggota keluarga, terutama anak-anak, untuk lebih mudah beradaptasi dengan perubahan yang terjadi. Intervensi yang berfokus pada tiga faktor ini terbukti mempercepat proses pemulihan dan adaptasi. Penelitian ini menekankan pentingnya mendukung keluarga melalui pendekatan sistematis dan terarah untuk meningkatkan resiliensi serta mengurangi dampak negatif perceraian.